Legality of Anesthesia Assistance in Surgical and Anesthesia Health Services in Hospital - Bambang Eko Prasetyo; Sutarno Sutarno; Asmuni (JILPR Journal Indonesia Law and Policy Review, 2023)
There is a demand from the community for quality health services, but the number of anesthesia service providers is still small. This poses a problem considering that it is the anesthesiologist who must accept the delegation of authority for medical anesthesia procedures. From these problems, this research aims to analyze the arrangements for assisting anesthesia services in hospitals and analyze the legal consequences for hospitals that employ health workers in anesthesia services that are not in accordance with competence and statutory regulations. This research method uses a normative juridical approach with statutory, conceptual and comparative approaches. The results showed that anesthesia services were only recognized after having applied a bachelor's degree in anesthesiology nursing and having certification in the form of Anesthesia Administration Registration Certificate and Anesthesia Management Practice License which are renewed every 5 years. Anesthesia service assistants who have a certificate must be able to carry out their professional authority responsibilities which include pre-anesthesia, intra-anesthesia and post-anesthesia authority by applying 5 competency standards which include legal ethics and patient safety; self-development and professionalism; effective communication; scientific basis of biomedical sciences, anesthesiology, and instrumentation; and clinical skills.